Digital poetics in the classroom: The role of Taroko Gorge in increasing students’ engagement and critical thinking skills - Bannaga Taha Al-Zubair Hussen; Cut Irna Liyana; Nadifah (Lingua Technica: Journal of Digital Literary Studies, 2025)
The integration of generative e-poetry like Taroko Gorge into literary education addresses the growing need to bridge traditional and digital literacy in contemporary learning environments. This study aims to explore how Taroko Gorge enhances students’ engagement and critical thinking, and to identify the possible strategies for its integration into curricula. Using a qualitative approach, this research combines observations, documentation, and interviews with 85 English Literature students at a university in East Java. The findings of this study reveal that Taroko Gorge fosters high levels of engagement and analytical rigor while challenging students to adapt to dynamic textual interpretations. Effective integration strategies include interactive discussions and scaffolded analysis, which align with its generative nature. However, limitations in interdisciplinary applications and sample diversity suggest the need for further research. This study contributes to pedagogical innovation by positioning e-poetry as a transformative tool for modern literary education.